LEGAL MIGRATION – RIGHTS AND BENEFITS IN THE EUROPEAN SOCIAL SECURITY SYSTEM - Nicoleta ANDRICA; Andreea-Florina FORA (Annals of the University of Oradea: Economic Science)
: In the present paper we are discussing about legal migration inside U.E and the rights it confers. All the states members are facing migration, which is a complex of challenges, including demographic, political and economics -one of the most important, the decrease in the labour market. Every country needs to attract skills and knowledge from abroad. Innovation and transition to a green and sustainable economy is a priority for all. We also approach the peculiarities and the characteristics of European digitalisation in social security coordination in all institutions in E.U., including Romania. In 2023, more than are 17 million of Europeans citizens are working or living abroad. European Union provides information for all the workers: equal treatment, E.U. legislation, rules for each one, rights in each country and also for family members. The countries implement the European interoperability for social security institutions, to make easier the electronic exchange between the institution from all Europe. Using this type of communication, mandatory for all members countries, gradually will be removed the documents on paper support by electronic one. This is part of green economy. EESSI (Electronic exchange of social security information) is use in different branch of social security such as unemployment, old age pension, accidents at work or sickness benefits, family benefits, or maternity and paternity benefits. Labor migration is a very important aspect of European Politics. Thus, the growing flow of foreign workers, who must benefit from all the rights conferred by European citizenship, accelerate the process of using these programs, to facilitate access to all this in shortest possible time and no additional costs.